Natural history clues to the evolution of bivalved gastropods (Mollusca: Gastropoda: Sacoglossa: Juliidae) - Wong, Nur Leena Wai Sin; Sigwart, Julia D. (Springer, 2019)
Bivalved gastropods (family Juliidae) are a pan-tropical group of small, green, extraordinary gastropods with a symmetrical clam-like shell. Only a single species of Juliidae has been reported in Malaysia, Berthelinia singaporensis Jensen, 2015, feeding on multiple species of siphonous green algae in the genus Caulerpa. In spite of a baseline expectation for megadiversity in this region, including 13 recorded species in the genus Caulerpa from two small field sites studied here, B. singaporensis appears to be a relative generalist without preferences among available Caulerpa spp. that occur in suitable (micro)habitats. The life cycle of Juliidae includes univalve, coiled larvae that transform to bivalved adults. In the presence of Caulerpa, swimming veligers rapidly settle and begin feeding; in a later, terminal metamorphosis, the larval operculum is shed, and the teleoconch shell field splits to form a second, right valve of the adult bivalved form. By three days after hatching, settled larvae achieve a fully functional bivalved shell with a working hinge. Both veligers and adults produce an unusual elastic mucous tether to maintain attachment to the substratum or food plant. These animals are dependent on Caulerpa for their entire life cycle; so, adults occupy environments where dislodgement may be a substantial risk. In the adult, bivalved, form, the gastropod can withdraw completely into its shell and close the valves while maintaining the byssus-like tether. This arrangement, enabling the gastropod to be simultaneously anchored to the food plant and protected within the shell, suggests that being able to use a byssus is the most plausible adaptive explanation for the evolution of the bivalved form within gastropods.